Connecting the Sustainable Development Goals: The WEF Nexus Understanding the Role of the WEF Nexus in the 2030 Agenda - Cavalli, Laura; Vergalli, Sergio (Cham : Springer International Publishing : Imprint: Springer, 2022)
This contributed volume offers a state-of-the-art, holistic overview of the employment of a Water-Energy-Food (WEF) Nexus approach to implement the seventeen United Nations Sustainable Development Goals (SDGs), with a geographical focus on applications in different African regions. The book is divided into three sections, each composed of several chapters contributed by experts in their respective fields. Section I introduces the WEF Nexus and its role in the achievement of the 2030 Agenda and the SDGs. It highlights the attempt to connect different spheres of sustainability thanks to the Nexus, taking advantage of the existing interlinkages and interconnections among the Goals. Section II proposes a multi-scale and multi-stakeholder approach to various aspects of the Nexus and reviews existing quantitative tools. This section focuses on the issue of resource control and development aims and spotlights how Nexus dynamics influence the achievement of the SDGs as a whole. Section III applies the WEF Nexus to different African regions, which are balancing a rising population and an economic boom with severe vulnerability in the face of climate change.
SectionI. WEF Nexus and 2030 Agenda for Sustainable Development: Overview -- Chapter1. The 2030 Agenda for Sustainable Development and the WEF Nexus -- Chapter2. Partnership for Research and Innovation in the Mediterranean Area and the Promotion of a Nexus Approach -- SectionII. Analytical Tools for SDGs Implementation within the WEF Nexus Framework -- Chapter3. SDGs and WEF nexus: A critical review of the analytical tools -- Chapter4. Review of the economic impact of water availability on food security and the related ecosystems -- Chapter5. Strengthening Water-Energy-Food Nexus through Multi-Stakeholder Engagement for Sustainable Food Systems -- SectionIII. A WEF Nexus Approach for SDGs Achievement in Africa -- Chapter6. Water-Energy-Food Nexus Resilience and the Sustainable Development Goals -- Chapter7. Multi-scale challenges in the Food-Energy-Water nexus -- Chapter8. Modelling the WEF Nexus to support Sustainable Development: An African Case.
Keywords: Sustainability; Environmental policy; Sustainability; Environmental Policy